RURAL TOURISM, AGROTOURISM AND ECOTOURISM IN ROMANIA: CURRENT RESEARCH STATUS AND FUTURE TRENDS - Mirela STANCIU; Agatha POPESCU; Cristian STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This work represents a contribution to the knowledge of the state of research in the field of rural tourism, agritourism and ecotourism in Romania, identifying the main trends and proposing future research lines and themes. Secondary data such as journal articles, proceeding papers reports and statistical data were analysed to obtain an image of the current stage in research with the topic rural tourism, agritourism and ecotourism in Romania. A systematic bibliometric analysis was conducted on the literature retrieved from the Web of Science Core Collection database using the VOS Viewer software tool. Using the specific keywords “Rural Tourism”, and “Agrotourism”, and ”Agritourism” and ”Ecotourism”, and ”Romania” 440 articles were reviewed and analysed. The results show that studies concerning these keywords and their influence on the development of rural areas in Romania represent an important and dynamic research topic in the last 10 years. Eight major research themes were identified regarding rural tourism, agritourism and ecotourism in Romania. The findings made in this paper will add to the existing body of knowledge of Romanian tourism research in general and, rural tourism research in particular.